Rooftop Solar Photo Voltaic Power Plant Design and Analysis with PVSyst Software - Veerraju, Mortha Sai; Rao, Yadavalli S. V. Venkateswara (Rooftop Solar Photo Voltaic Power Plant Design and Analysis with PVSyst Software, 2021)
Solar Roof top Photo Voltaic systems are being progressively used worldwide now a days to install solar panels to generate electricity. The design of power plant for generation of power through solar roof tops to install a 33KWp on-grid solar power system with Latitude 16.54°N and Longitude 81.50°E for the grid connected PV system is installed at an area of 345 sq. m and the PV modules are tilted at an angle of 18° on the top of a 3 staired building. This book covers the design and analysis of the Performance of a 33KWp On-grid photovoltaic system which is monitored between Jan-2019 to Dec-2019. This also analyses the Design and performance of 39.2KW grid connected PV system at another block of the building. The 39.2KW grid connected system is proposed to be installed on the top of a 5 staired building. The grid connected PV system with a capacity of 39.2KWp is proposed based on the user’s needs which consists of 3 case studies for the same plant with different orientations namely fixed tilt, seasonal tilt and N-S axis tracking. Based on these case studies the optimal tilt angle for the installation of PV plant can be selected. The different case studies of field orientations are analysed with different parameters. The Performance of these On-grid photovoltaic systems during an entire year are analysed and the performance parameters are measured. The data is analysed by using the simulation software PVsyst. The different parameters including efficiencies of module, inverter, array’s initial yield, final array yield, and the performance ratio of PV system are analysed for the 3 case studies.